Solar hydrogen production using epitaxial SrTiO3 on a GaAs photovoltaic. Issue 1 (6th January 2017) - Kornblum, L.; Fenning, D. P.; Faucher, J.; Hwang, J.; Boni, A.; Han, M. G.; Morales-Acosta, M. D.; Zhu, Y.; Altman, E. I.; Lee, M. L.; Ahn, C. H.; Walker, F. J.; et al.
Abstract : We demonstrate an oxide-stabilized III–V photoelectrode architecture for solar fuel production from water in neutral pH. Abstract : We demonstrate an oxide-stabilized III–V photoelectrode architecture for solar fuel production from water in neutral pH. For this tunable architecture we demonstrate 100% Faradaic efficiency for hydrogen evolution, and incident photon-to-current efficiencies (IPCE) exceeding 50%. High IPCE for hydrogen evolution is a consequence of the low-loss interface achieved via epitaxial growth of a thin oxide on a GaAs solar cell. Developing optimal energetic alignment across the interfaces of the photoelectrode using well-established III–V technology is key to obtaining high performance. This advance constitutes a critical milestone towards efficient, unassisted fuel production from solar energy.